REVIEW OF THE JUDICIAL PRACTICE OF THE SERBIAN SUPREME COURT AND COURTS OF APPEAL IN FAMILY MATTERS - Stojanovic, Natasa (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
Almost twenty years have passed since the Family Law of the Republic of Serbia was adopted. It is a chance to address its application in practice, especially through the functioning of the Supreme Court of and the courts of appeal. In her paper, the author provides a summary overview of the court practice of these judicial instances in family law matters, since the start of application of the Family Law until today, and all her attention is focused particularly to family law institutes the application of which has proved to be the most controversial in practice. These are legal status of cohabitation, establishing child’s origin, deprivation of parental rights, support, property relationships within family, and domestic violence. The author in her paper, using primarily the method of content analysis (courts’ decisions), but also legal and dogmatic, normative and legal, and historical and legal methods, through an analysis of some selected rulings of the Supreme Court and the courts of appeal of the Republic of Serbia, also finds and highlights the differences in viewpoints of such courts relating to almost identical family matters, implicates disparities in the functioning of the same court instance regarding such identical controversial family law case and an unequal treatment of parties in proceedings thereof. In the author's understanding, a large number of controversial family law cases in the domestic judicial practice is a real indicator of the collapse of family as the basic cell of the society and it can be reduced, from the legal point of view, by “eliminating” the observed uncertainties and inaccuracies in the Serbian Family Law, providing some guidelines for a closer determination of the used legal standards and filling all the legal gaps observed by the court practice and theory. Additionally, it is necessary to create, along with the existing ones, a new legal mechanism that would contribute to a more quality court practice harmonisation in the domain of civil law matter in the Republic of Serbia.
Keywords: family-law relationships; Family Law; court practice